PENETAPAN NILAI KETIDAKPASTIAN BAKU SISTEM PENGUKURAN METODE TIDAK LANGSUNG SATUAN KELISTRIKAN DAYA SATU FASA PADA SKALA LABORATORIUM - Hadi Sardjono (JURNAL STANDARDISASI, 2006)
As a national laboratory, Puslit KIM-LIPI has been realised it measurement capability for ac power in form of Power Source System which is performed in combination of an ac voltage source, an ac current source and a pahse shifter from 00 up to 3600. Concerning to the accuracy maintenance, it was observed by using an indirect measurement method. This measurement system was involved a several equipment standards such as a DMM (Digital Multimeter) and a wattmeter as the load and the voltage and the current value supply by the power source were measured with it accuracy limmitation up to 0.8%.